The Violation of Principles of Linguistic Politeness in Javanese Speakers of the Banyumas Dialect: Studies of Sociopramgmatics - Setiawan, Tri Indo; Zulaeha, Ida (Universitas Negeri Semarang, 2021)
The Banyumas dialect of the Javanese language (ngapak) was the Javanese language that is used by most people in Banyumas. The Banyumas dialect of the Javanese language (ngapak) had its uniqueness, namely its cablaka or frank-speaking nature. It was created a stereotype that ngapak speakers were not educated to speak or violate the principle of education. The cablaka character was a form of showing that Banyumas people prefer to express their opinions and thoughts frankly and without chattering or hiding anything. The purpose of this study was to analyze the form of violation of the principle of courtesy in the spoken language of Javanese speakers of the Banyumas dialect (ngapak). This study was located at Desa Samudra, Kecamatan Gumelar, Kabupaten Banyumas. This research was used a theoretical approach namely a pragmatic approach and a methodological approach was a qualitative descriptive approach. The data collected in this study used the listening method, followed by conversational engagement, recording, and note-taking techniques. The data were analyzed using the matching method with the basic technique of sorting the determining elements. The results of this study indicate that there was a violation of the principle of courtesy in the spoken language of the Javanese-speaking community of the Banyumas dialect (ngapak). The violation has found including (1) the maxim of wisdom (tact maxim); (2) maximum of generosity (generosity maxim); (3) maximum of approval (approbation maxim); (4) maximum of modesty (modesty maxim); (5) maximum of agreement (agreement maxim); (6) maximum of sympathy (sympathy maxim).